Spatial and temporal variability in grassland structure associated with different densities of the white rhinoceros (Ceratotherium simum) in a South African savanna - Malmström, Emilia (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
The direct and indirect relationships between species in different trophic levels are referred to as trophic dynamics and are important in maintaining the function of ecosystems. Megaherbivores may have effects both directly and indirectly on other species since their impact may be disproportionately large relative to their population size. Megaherbivores are therefore often considered as keystone species. The white rhinoceros in Africa (Ceratotherium simum) has previously been described as a keystone species and ecological engineer as a mega grazer in the African savanna. This study investigated the role of white rhino and the indirect effect of white rhino poaching on savanna grassland structure. I measured the proportion of lawn grass cover and grass biomass across gradients of white rhino density and poaching intensity on 30 different sites in Hluhluwe‐iMfolozi Park in the province of Kwa‐Zulu Natal in South Africa. Grass biomass decreased and lawn grass cover increased with increasing white rhino presence (rhino local use), suggesting that white rhino act as an important driver in creating and maintaining grazing lawns and grassland structural heterogeneity. All models also suggest that grass biomass and lawn grass cover were more strongly correlated with presence of other herbivores than with white rhinos, which might indicate that white rhinos are not the main creators of grazing lawns and that other herbivores also play an important role in maintaining lawns. Grass biomass decreased and lawn grass cover increased as poaching of white rhinos increased which may indicate that poaching intensity is high where white rhino density is high. However, these results may suggest that white rhinos increase grassland heterogeneity and the disruption of this function through poaching could have far‐reaching consequences for the availability of grassland habitat for other species.